Rancangan Kolase Digital melalui Konsep Waktu Linier pada Film Dokumenter “Nasida Ria: Sun Stage” (2023) Karya Wisnu Candra - Wisnu, Candra Mohammad; Armantono, R. B. (LITERATUS, 2024)
Not only recording reality, the form of documentary films today has undergone significant development. One of the drivers of development is the digital phenomenon. Digitalization is not an impact, but a phenomenon that must be adapted as best as possible and addressed as wisely as possible. The purpose of this development is to provide innovation in the form of documentary films that are more innovative and creative. Qualitative method is used as the epistemology of data collection through research to validate the truth of the subject. Meanwhile, the principle of cross-disciplinary collaboration between film directors and digital collage artists is used as a foundation to produce a visual identity for the film to be more innovative and creative. As a result, the short film "Nasida Ria: Sun Stage" is not only a film that records the history of Nasida Ria, but also a contribution to the evolution of the documentary film form. Through an archive of texts, photos and videos arranged using digital collage techniques and moved linearly.